2014
DOI: 10.1038/bmt.2014.232
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of treatment strategies in ex vivo T-cell-depleted haploidentical SCT for pediatric patients

Abstract: We evaluated the feasibility of T-cell-depleted haploidentical hematopoietic SCT (HHCT) in pediatric patients. Between July 2008 and January 2013, 28 patients underwent ex vivo T-cell-depleted HHCT; 9 had hematologic malignancy, 18 had nonmalignant hematologic disease, and 1 had refractory neuroblastoma. Twenty-six patients achieved neutrophil engraftment at a median of 11 days (range, 9-15 days). Two patients failed to achieve primary engraftment and five experienced graft rejection after primary engraftment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…6,[10][11][12][13][14][15] There have been several reports on HHCT in pediatric patients. 4,5,7,[16][17][18] In our current study, all 42 patients achieved stable engraftment early post transplant at a median of 10 days. No patient experienced graft failure (GF), including late GF.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…6,[10][11][12][13][14][15] There have been several reports on HHCT in pediatric patients. 4,5,7,[16][17][18] In our current study, all 42 patients achieved stable engraftment early post transplant at a median of 10 days. No patient experienced graft failure (GF), including late GF.…”
Section: Discussionmentioning
confidence: 95%
“…7 Our previous study with CD3-depleted HHCT showed a rather high incidence of GF in the early period of the study; therefore, we modified the targeted dose of T cells in different ranges to improve the outcomes. Another practical issue was that the reduction of T cells is less effective with the CD3-depletion method and frequently leads to residual T cells in the graft that exceed the threshold of 5 × 10 4 /kg, requiring immunosuppressive drugs to prevent GvHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, ex vivo T-cell depletion of CD3 cells or even αβ+ T-cells plus B-cell depletion using the CliniMACS ® system (Miltenyi Biotec, Bergisch Gladbach, Germany) has been introduced successfully [44,45]. Most strikingly, Im et al [46] reported excellent survival of 100 % for 12 AA patients after CD3-depleted HSCT in Korean children.…”
Section: Haploidentical Family Donor (Hfd) Hsctmentioning
confidence: 99%